The Impact of Three-Step Interview towards Students’ Speaking Skill at the Eleventh Grade of Senior High School Adhyaksa 1 Jambi - Annisha Annisha; Yanti Ismiyati; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2023)
This research was made to find out whether there is any good impact after the Three-Step Interview Method was applied to the students of the eleventh grade of Senior High School Adhyaksa 1 Jambi. This research used quantitative method, and true experimental design to approach the students with pretest-posttest control group design. Through simple random sampling technique, the researcher took 48 students as the sample of this research, with the total population of 140 students. XI MIPA 1 was chosen as the control class and XI MIPA 2 as the experimental class. The technique of distributing the data was speaking test where the students were asked to give their opinion using English through the given case, with pre-test, treatments, and post-test. This research used t test as the data analysis technique with Statistical Package for the Social Sciences (SPSS) for Windows version 21 program. The results that were found in this research are: (1) students’ speaking skill taught by using the Three-Step Interview method reached the mean of 20,00; (2) students’ speaking skill taught by using the normal group discussion method reached the mean of 19,21; (3) students’ speaking skill taught by using the Three-Step Interview method is higher than students’ speaking skill taught by using the normal group discussion method with a value of Sig. 0.000 > 0.05. Therefore, there is a significant impact in using Three-Step Interview for the students’ speaking skill.